Antenatal care utilisation among adolescent mothers in Ngozi Province, Burundi (2024)
Background: Globally pregnancy and childbirth complications are the leading cause of death among adolescents, with evidence showing that antenatal care (ANC) is a very effective preventive intervention. In Burundi, there is limited information on the extent to which pregnant adolescents utilise such services. Objective: To assess the ANC utilisation and factors associated with its use among adolescent mothers in Ngozi Province, Burundi. Materials and Methods: A cross-sectional, health facility-based study among 216 adolescent mothers who had given birth within two years preceding this study, using structured questionnaires and records from previous ANC booklets. A multistage random sampling technique was used to select respondents while the utilisation of ANC was determined by the frequency of ANC visits and the time when the women enrolled for the first ANC visit. Results: The majority (98.1%) of adolescent mothers in Ngozi Province used ANC services. Most respondents (64.8%) initiated ANC services within the first trimester while 57.8% attained the minimum of four recommended ANC visits. Marital status (P = 0.001), geographical location (P = 0.009), occupation of the partner (P = 0.002) and type of the last pregnancy (P = 0.012) were associated with ANC initiation within the first trimester while marital status (P < 0.001), respondent’s employment (P = 0.003) and type of last pregnancy (P < 0.001) were associated with appropriate ANC frequency. Conclusion: This study revealed a high use of ANC services among adolescent mothers, although more than one-third attended ANC late. There is therefore the need to put more effort into improving early booking for ANC.